SCABIES AND ITS MANAGEMENT; A CASE REPORT - Suryani Prasetyo, Gabriella Nindya (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana, 2013)
Scabies is one of skin disease that caused by Sarcoptes scabei var, hominis . Scabies is easily spread out andvery itchy especially at night. This disease happened globally and related to bad hygiene and high population.The cycle of scabies mite started from egg untill mature needs 8-12 days. There are four cardinal signs of scabies, consists of nocturnal pruritus, attacks groups of people, there is cunicullus on predilections place, mites found which will be diagnostic sign. The treatment use topical 5% permetrin cream and also  maintain body hygiene.
Keywords: scabies, sarcoptes, permetrin